Influence Ecosystem Orchestration and Cross Sector CollaborationTowards Improving the Performance of MSMEs in North Rawa Badak - Irawan, Pristanto Ria; Taryanto, Taryanto; Hisna, Wa Ode (Business Management, 2025)
This study seeks to examine the effects of ecosystem orchestration and cross-sector collaboration on enhancing the performance of MSMEs in Rawa Badak Utara Village, North Jakarta. In light of economic instability and market fluctuations in metropolitan regions, MSMEs must forge robust partnerships with many stakeholders within their business ecosystems, including government entities, the private sector, educational institutions, and local communities.  This study employed a quantitative methodology via a survey of 76 MSMEs across diverse business sectors. Data were collected via a structured questionnaire and analyzed employing a multiple linear regression model.  The research findings demonstrate that ecosystem orchestration exerts a substantial partial influence on MSME performance, although cross-sector collaboration does not exhibit a significant individual effect. Both variables concurrently exert a positive and significant influence on enhancing MSME performance in the investigated area.  This study significantly contributes to the development of collaboration-based policies aimed at fostering the growth of MSMEs in urban areas, namely in the Rawa Badak Utara Subdistrict of North Jakarta.